Management Measures and Trends of Biological Invasions in Europe: A Survey‐Based Assessment of Local Managers - Garcia‐Lozano, Carla; Pueyo‐Ros, Josep; Canelles, Quim; Latombe, Guillaume; Adriaens, Tim; Bacher, Sven; Cardoso, Ana Cristina; Cleary, Michelle; Coromina, Lluís; Courchamp, Franck; Dawson, Wayne; de Groot, Maarten; et al. (Wiley-Blackwell, 2025)
Biological invasions are a major threat to biodiversity, ecosystem functioning and nature's contributions to people worldwide. However, the effectiveness of invasive alien species (IAS) management measures and the progress toward achieving biodiversity targets remain uncertain due to limited and nonuniform data availability. Management success is usually assessed at a local level and documented in technical reports, often written in languages other than English, which makes such data notoriously difficult to collect at large geographic scales. Here we present the first European assessment of how managers perceive trends in IAS and the effectiveness of management measures to mitigate biological invasions. We developed a structured questionnaire translated into 18 languages and disseminated it to local and regional managers of IAS in Europe. We received responses from 1928 participants from 41 European countries, including 24 European Union (EU) Member States. Our results reveal substantial efforts in IAS monitoring and control, with invasive plants being the primary focus. Yet, there is a general perception of an increase in the numbers, occupied areas, and impacts of IAS across environment and taxonomic groups, particularly plants, over time. This perceived increase is consistent across both EU and non-EU countries, with respondents from EU countries demonstrating more certainty in their responses. Our results also indicate a lack of data on alien vertebrates and invertebrates, reflecting a need for more targeted monitoring and knowledge sharing between managers and policymakers and between countries. Overall, our study suggests that Europe's current strategies are insufficient to substantially reduce IAS by 2030 and hence to meet the Kunming-Montreal Global Biodiversity Framework target.
Keywords: vieraslajit; hallinta; seuranta; havainnointi; kyselytutkimus; invasive species; management (control); monitoring